The Effect of Earnings Management on Company’s Performance with Audit Quality and Company’s Size as Moderating Variables - Aprih Susanto; Rahmatya Widyaswati (Telaah Bisnis, 2019)
Abstract The purpose of this study was to see how the effects of earnings management on the performance of companies with audit quality and size of the company as a moderating variable. High Quality Audit demonstrated with large or small public accounting firm. The size of the company can be seen from how many assets owned by the company itself. The sample in this study is based on purposive sampling, with specific criteria that a manufacturing company listed on the Stock Exchange during the period 2011-2014 which publishes annual financial statements (annual report) in complete accordance with the measurement variables to be studied in this research, manufacturing company whose financial statements are audited by KAP Big 4 and non- Big 4. So in the get the 22 companies audited by the Big 4 accounting firm and the 28 companies audited by KAP Non Big 4. The results of this study variable Profit Management significant negative effect on the performance effect Perusahaan. VariabelCompany’s Size significantly strengthen the positive relationship between Profit Management with Corporate performance. Variable Audit Quality significant positive effect strengthens the relationship between the Profit Management with Corporate Performance.